DEVELOPMENT OF A COMPREHENSIVE ONE HEALTH TICKBORNE DISEASE SURVEILLANCE WEBSITE AND INFORMATIONAL BROCHURES FOR THE STATE OF KANSAS - Thomason, Sasha (My University, 2021)
Cases of tickborne diseases in people and animals are on the rise. Additionally, emerging and re-emerging tickborne diseases are being discovered at a rapid rate. The growing human population, global trade and travel, an increase in pet ownership, and changes in the geographical distribution of ticks are contributing factors that will cause this trend to continue. Veterinarians and physicians need to ensure they are knowledgeable about tickborne diseases, the diagnostic tests used to confirm these infections, the proper treatment of these infections, and the information that needs to be relayed to patients and pet owners for their education and protection. A One Health approach is needed to bring veterinary and human health information together in one place for easy access by both disciplines. Information about the ticks present in the state of Kansas, the diseases they carry, and the location of human and animal cases are diagnosed would help meet this need. A comprehensive One Health tickborne disease surveillance website for the state of Kansas was developed as a result.
Keywords: tick-borne disease; Kansas Department of Health and Environment; Spotted fever group Rickettsiosis; Lyme Disease; Tularemia; Rocky Mountain spotted fever